Association Between Vitamin D Deficiency and Recurrent Wheezing in Children - Naseem, Ayesha; Ashraf, Sohail; Safdar, Shiza; Zafar, Yumna; Alvi, Hajra Iqbal (Indus Journal of Bioscience Research, 2025)
Background: Vitamin D plays a crucial role in immune regulation and respiratory health, with its deficiency being implicated in recurrent wheezing among children. Given the high prevalence of vitamin D deficiency in pediatric populations, understanding its association with recurrent wheezing can guide preventive and therapeutic strategies. Objective: The objective of the study was to determine the frequency of vitamin D deficiency among the children with recurrent wheezing. Study Design: Cross-sectional study. Duration and Place of Study: The study was conducted between March 2024 to September 2024 in the Pediatrics Department of POF Hospital Wah Cantt. Methodology: A total of 95 children aged 2–5 years, with a history of at least three wheezing episodes in the past year, were included. Children with clinical rickets, prior vitamin D supplementation, or chronic illnesses affecting vitamin D metabolism were excluded. Serum 25(OH)D levels were measured using an ELISA kit and categorized as sufficient (>30 ng/mL), insufficient (21–29 ng/mL), or deficient (<20 ng/mL). Results: The mean age of participants was 3.49 ± 1.09 years, and the mean serum vitamin D level was 26.93 ± 9.36 ng/mL. Among the children, 56.8% were male, and 43.2% were female. Vitamin D deficiency was found in 27.4% of children, while 30.5% had insufficient levels, and 42.1% had sufficient levels. Younger children (2–3 years) exhibited a higher deficiency rate (35.4%) than older children (4–5 years) (p=0.003). Conclusion: Vitamin D deficiency is prevalent among children with recurrent wheezing and is significantly associated with younger age, female gender, and lower socioeconomic status.